Społeczny odbiór debat przedwyborczych kampanii parlamentarnej 2011 - Jaruga, Kinga; Krawczyk, Żaneta (Political Preferences, 2012)
Pre-election TV debates are not merely a means of providing information. Their pri- mary objective is the implementation of carefully formulated marketing strategy. The process of making politics personalized and entertaining undoubtedly contributes to the surge in their popularity. They become not only a means of conveying the information included in election manifestos or outlining the profiles of candidates. They create a kind of show, based on specific rules and a top-down program, designed to reach out to voters effectively.Public opinion polls clearly show that the evaluation of the effectiveness of such pro- grams is strongly correlated with the declared policy preferences. This article presents an im- age of pre-election debates with the use of the 2011 parliamentary campaign. The main aim of the discussion is to answer the question of whether pre-election television debates are an effective way of reaching out to voters. The second aspect of the analysis is the context of "the debate over the debate", which gives a specific character to the events described.